PENGARUH PENAMBAHAN KANGKUNG AIR (Ipomoea aquatica) PADA PAKAN TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus) Effect of adding water kale (Ipomea aquatica) to feed for the weight of tilapia (Oreocromis niloticus) - Rianda Putra; Eri Yusni; Irwanmay Irwanmay (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
Tilavia is favorite fish consumsion by the people of indonesiaand it is very easy to cultivate because it has a sufficient level of the prospective development. The feed is a very important factor in the process enlargement fish. This research was conducted to determine the effect of feeding a mixture of pellets water kale on the growth of tilapia. Container maintenance of tilapia used mine concrate pols with 1 x 1 x 1 M2 of size and 50 liters of volume water for each pool.This research was conductedin August – November 2015 in the Binjai Town. The method user completely randomized design with treatment of pellets feed was + kale (1:3). The P1 treatment showed the best daily length growth and daily weight growth. The final result obtained the length of P1 treatment was 11,76 cm, P2 treatment was 10, 92 cm, P3 treatment was 9, 97cm, and the weight of P1 treatment was 13,15 gr, P2 treatment was 11,21 gr, P3 treatment was 9,66 gr. The total feed used 3966.9 gr.Key Words : Tilapia (Oreocromis niloticus), Growth, Water Kale (Ipomea aquatica)